Genome Sequence of Chthoniobacter flavus Ellin428, an Aerobic Heterotrophic Soil Bacterium - Kant, Ravi (American Society for Microbiology, 2011)
Chthoniobacter flavus Ellin428 is the first isolate from the class Spartobacteria of the bacterial phylum Verrucomicrobia. C. flavus Ellin428 can metabolize many of the saccharide components of plant biomass but is incapable of growth on amino acids or organic acids other than pyruvate.